Sistem Pembelajaran Discord Flipped Classroom Berbasis Guided Inquiry Dengan Literasi Digital untuk Mahasiswa Kimia Tahun Pertama - Intan Nofita Sari; Mawardi Mawardi; Reza Akmar; Alizar Ulianas; Okta Suryani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a valid and practical learning system in addressing the need for an instructional design that fosters digital literacy in first-year chemistry students. Using the Educational Design Research framework, the learning system was developed on Discord and integrated flipped-guided inquiry learning models. The study involved lecturers and students from Department of Chemistry, Universitas Negeri Padang. The system was structured with a server and channels to facilitate each stage of the learning process. The evaluation assessed the validity and practicality of the system. The overall results indicated the system was highly valid with overall validity of 0.85 (construct validity 0.85 and content validity 0.86) and practical (student practicality 81% and lecturer practicality 83%). These findings suggest that a Discord-based, flipped-guided inquiry system is a highly viable and useful tool for teaching thermochemistry and student’s digital literacy.